Scroll, Click, Checkout: Does Visual Appeal Take Women's Attention to Buy Impulsively? - Emirah Hayati; Muhartini Salim (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2025)
Purpose: This study investigates how visual appeal in e-commerce influences impulse buying among women, with browsing behavior as a mediating factor. It explores how the appearance of e-commerce applications facilitates both hedonic and utilitarian browsing, which may lead to impulse buying.Method: This study used a quantitative approach by distributing online questionnaires via Google Forms through social media. The sample included 170 Gen Z and Millennial women aged 17–44 years who use Shopee in Indonesia. We analyzed the data using Structural Equation Modeling with the Partial Least Squares (PLS-SEM) method in SmartPLS4.Result: The results show that visual appeal significantly influences both hedonic and utilitarian browsing. Only hedonic browsing directly drives impulse buying. Visual appeal and utilitarian browsing do not significantly affect impulse buying. Moreover, hedonic browsing fully mediates the effect of visual appeal on impulse buying, while utilitarian browsing does not act as a significant mediator.Practical Implications for Economic Growth and Development: This study emphasizes the importance of visual design in e-commerce platforms. Appealing visuals enhance users' enjoyment during hedonic browsing, increasing the chance of impulse buying. By creating engaging visual experiences, developers and sellers can foster user satisfaction, loyalty, and sales growth.Originality/Value: This study offers new insights by focusing on Gen Z and Millennial women in Indonesia—an underrepresented group in e-commerce research. It also clarifies the distinct mediating roles of hedonic and utilitarian browsing in the relationship between visual appeal and impulse buying.